Legacy of a distinguished scientist: George E. Palade - Singer, Manfred V. (Pancreatology, 2003)
Porosomes are secretory portals located at the cell plasma membrane involved in the regulated release of intravesicular contents from cells. Porosomes have been immunoisolated from a number of cells including the exocrine pancreas and neurons, biochemically characterized, and functionally reconstituted into an artificial lipid membrane. In the current study, the proteome of the porosome complex in mouse insulinoma Min6 cells was determined, demonstrating among other proteins, the presence of 30 core proteins including the heat shock protein Hsp90. Half maximal inhibition of Hsp90 using the specific inhibitor 17-demethoxy-17-(2-prophenylamino) geldanamycin, results in the loss of proteins, including the calcium-transporting ATPase type 2C and the potassium channel subfamily K member 2 from the Min6 porosome. This loss of porosome proteins is reflected in the observed inhibition of glucose stimulated insulin release from Min6 cells exposed to the Hsp90 specific inhibitor. Results from the study implicate Hsp90 in the assembly and function of the porosome complex. - In the present study, the porosome proteome in the insulin-secreting mouse β-cell line Min6 has been determined. Nearly 30 core proteins including the heat shock protein Hsp90 are found to compose the Min6 porosome complex. Results from the study implicate Hsp90 in the assembly of the Min6 porosome. These new findings will facilitate understanding of the porosome assembly and its function in insulin secretion.